Peningkatan Mutu Tenaga Keolahragaan Guru Penjas Sekecamatan Sidareja - Restian Gigih Sejati; Rama Cipta Prasetia; Miftahul Hidayat (Pusat Riset dan Inovasi Nasional, 2021)
Community service is non-formal education for physical education teachers in schools, through educational activities, and educational outreach that can support community development. Education for the community is one of the implementations of the tri-dharma of higher education. Community service through seminars on Improving the Quality of Sports Personnel for Physical Education Teachers in Schools in Sidareja District is an effort to: (1) find out and provide an understanding of the level of knowledge of sports human resource management of physical education teachers in schools in Sidareja District; (2) knowing and describing the potential of sports human resources in schools throughout Sidareja District. This Community Service is carried out to provide education for physical education teachers in each school about understanding the basics of training procedures and identifying talents from an early age in schools to create a generation of high-achieving people. As a result of this community service, there is an increase in knowledge about skills in preparing training programs and understanding of identifying children's talents in looking for potential athletes in schools.